Children Who Lose a Parent in the COVID-19 Era: Considerations on Grief and Mourning. Issue 1 (31st December 2023) - Rice, Timothy
ABSTRACT: The death of a parent or caretaker presents children, adolescents, and young adults with an immense loss and challenge. Youth grieving and mourning requires review and reexamination from the perspective of our current times. Many youth have lost parents during the ongoing COVID-19 pandemic. Their parents' deaths stem from various causes of mortality, both related and unrelated to the SARS-CoV-2 virus. A parental death by COVID-19 presents a unique situation that contains elements which can lead to traumatic grief and disrupted mourning. Social distancing, travel restrictions, and shifts in funeral and memorial practices all affect avenues for successful mourning. Economic, social, and educational changes and family dysfunction associated with the pandemic have altered the normal supports available to a child in the process of mourning a parent. Knowledge of childhood grief and mourning are reviewed and revisited in light of these pandemic challenges. Opportunities for clinical interventions, both in traditional psychoanalysis and psychoanalytic psychotherapy as well as parent work and consultative roles to schools, hospitals, and other institutions, are discussed.